2020
DOI: 10.1093/tropej/fmz083
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malaria in Newborns Delivered to Mothers with Malaria-Infected Placenta in Blue Nile State, Sudan

Abstract: Diagnosis of congenital malaria is complicated by the low density of the parasite circulating in the cord blood and/or the peripheral blood of the newborns. Molecular techniques are significantly more sensitive than blood smears in detecting low-level parasitemia. This study investigated the prevalence of congenital malaria by the use of the real-time polymerase chain reaction (real-time PCR) in 102 babies born to mothers with microscopically confirmed infected placenta from Blue Nile state, Sudan. At delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
6
2
Order By: Relevance
“…In this study, a frequency of 12.2% (95%CI = 9.4-14.9) was found, which is lower than those reported in studies from Africa that used a similar case definition, that is, positive by TBS or PCR in peripheral or cord blood samples, in which prevalences between 18.6% and 56.8% were reported [7,11]. It is also totally different from studies that evaluated both blood samples with TBS, which reported frequencies of 6.1% [9] and 26.5% [10], and also from the figures of a meta-analysis in which no cases were reported for the Colombian studies (although this figure of 0.0 is consistent with the TBS results of the current study) [13].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In this study, a frequency of 12.2% (95%CI = 9.4-14.9) was found, which is lower than those reported in studies from Africa that used a similar case definition, that is, positive by TBS or PCR in peripheral or cord blood samples, in which prevalences between 18.6% and 56.8% were reported [7,11]. It is also totally different from studies that evaluated both blood samples with TBS, which reported frequencies of 6.1% [9] and 26.5% [10], and also from the figures of a meta-analysis in which no cases were reported for the Colombian studies (although this figure of 0.0 is consistent with the TBS results of the current study) [13].…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, others indicate that no clinical features were associated with CM (birth weight, gestational age, APGAR, length at birth, temperature, anemia), reporting association only with maternal parasitaemia, pregnancies (higher in primigravidae), maternal age (higher in those under 19 years of age) and placental malaria [9]. Other studies found an association with maternal age and hemoglobin, but not with parity, educational level, use of a mosquito net, area of residence, or neonatal weight [11]. While other authors only reported an association with the use of mosquito net [10].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Vector transmission of malaria parasites that occurs during the blood meal of an infected female anopheles mosquito is the most common mode of transmission [1,2]. However, other modes of transmission exist, including vertical transmission from infected mothers to their unborn babies (congenital malaria) [3][4][5][6], and horizontal transmission from infected blood donors to their recipients (transfusion-transmitted malaria) [7][8][9]. In fact, both congenital and transfusion-transmitted malarias are common and represent significant public health problems, particularly in areas with high stable transmission of Plasmodium falciparum [5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, another devastating consequence of P. falciparum infection in pregnant women is congenital malaria that remains a major global problem especially in the endemic regions ( Bilal et al., 2020 ; Danwang et al., 2020 ). Congenital malaria is defined as the presence of intraerythrocytic malaria parasites in the cord blood and/or the peripheral blood of an infant within the first week of birth, independent of display of the clinical symptoms ( Omer et al., 2020 ). Infected newborns often show nonspecific, sepsis-like clinical manifestations in which early treatment can result in diminished risk of complicated malaria.…”
Section: Disease and Symptomsmentioning
confidence: 99%